Evaluating the establishment success of Microctonus aethiopoides (Hymenoptera: Braconidae), a parasitoid of the alfalfa weevil (Coleoptera: Curculionidae), across the northern Great Plains of North America. Issue 2 (2nd February 2018) - Rand, Tatyana A.; Pellissier, Makenzie; Jabbour, Randa; Lundgren, Jonathan G.; Waters, Debra K.
Abstract: The alfalfa weevil ( Hypera postica (Gyllenhal); Coleoptera: Curculionidae), is a destructive pest of alfalfa ( Medicago sativa Linnaeus; Fabaceae) worldwide. The biological control parasitoid, Microctonus aethiopoides Loan (Hymenoptera: Braconidae), was successfully introduced, and considered highly effective, in the eastern and mid-western United States of America. Redistribution efforts carried out throughout the 1980s reported initial establishment in the northern Great Plains, however follow-up studies to assess long-term persistence and efficacy are lacking. We resurveyed the counties in which M. aethiopoides had been initially recovered following redistribution in Montana (Flathead and Petroleum counties), Wyoming (Platte County), and South Dakota (Brookings County), to gauge whether this species has become permanently established and, if so, assess levels of parasitism in the field. We collected adult weevils from five fields in each county, and reared them in the laboratory to assess parasitism. Despite rearing more than 1000 weevils, no parasitoids were recovered from any of the locations sampled in our study, suggesting a widespread failure of M. aethiopoides to persist in the region. Thus, M. aethiopoides does not currently appear to be an important biological control agent of alfalfa weevil in the northern Great Plains. More intensive surveys will be required to assess the extent of the distributional limits of this species throughout the region.